Morphological Observation, Identification and Isolation of Tropical Marine Microalgae from Ambon Bay, Maluku - Telussa, Ivonne; Hattu, Nikmans; Sahalessy, Arielno (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2022)
Microalgae are photosynthetic microorganisms that are widely distributed in waters. They have the potential as an alternative source of pigments, lipids, proteins, and carbohydrates. In this study, identification and isolation of single-cell microalgae from Ambon Bay were carried out by serial dilution method and inoculation of the culture by appearance/spread on the surface of the solidified agar medium. The results showed that the waters of Ambon Bay have physical parameters such as temperature, pH, salinity, and TDS, which are still within the threshold specified in the seawater quality standard for biota. The water conditions at the 10 sampling locations had different salinity, pH, temperature, and TDS. This condition affects the distribution of microalgae in the waters in Ambon Bay. The image from light microscopy shows that there are 27 species of microalgae scattered in the waters of Ambon Bay, which belong to the classes Chlorophyceae, Flagilariophyceae, Bacillariophyceae (diatoms), Coscinodiscophyceae, and Dinophyceae. Microalgae isolation obtained five species (single-cell) including four species from the class Bacillariophyta (Navicula sp, Nitzschia sp, Cyclotella sp) and one species from the class Chlorophyta (Chlorella sp).